Estimation of correlation and path coefficient for morphological and quality related traits in pea (Pisum sativum L.) (Bangladesh Journal of Botany, 2020)
Statistical analysis of variance, correlation and path coefficient for morphological and quality related traits such as number of nodes, pod width, seeds per pod and mature seed length showed significant positive correlation. Furthermore, mature seed weight and 100-seed weight at 13 - 15% moisture content had significant relation with the quality related traits i.e. starch contents, protein contents and zinc contents. Plant height and number of nodes had positive indirect effect on pod length, pod weight, pod thickness, number of seeds per plant, 100-seed weight and other yield related traits. While, mature seed weight, seed length and seed thickness had positive indirect effect on the quality parameters.